ALAT PENDETEKSI STRES PADA MANUSIA BERBASIS ATMEGA 32 - , MAYLIA PUTRI; , Drs. Panggih Basuki, M. Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Stress detector for human which is a digital electronics system with addressing methods IC programmed ATMega32 microcontroller by displaying three body condition score were used as the value of the stress parameter. Using the LCD display will be classified under four stress conditions are relaxed, calm, anxious and tense. Parameter values measurement based on body temperature, skin resistance and heart rate. deviation standard This stress detector works based on the results of data processing information sent by the three sensors. In this system, the three sensors are used to monitor the four conditions on the human body then controlled by a microcontroller which has been programmed using the C AVR programming language. The results of testing the system, performed three trials measurement of the three sensor to make comparisons against existing tools. This stress detector is able to classify the four parameters into the parameters of the state of the body level of stress with temperature sensor of 0,2 0 C, the heart rate sensor and a 0,4 bpm and deviation standard in GSR sensor by 0.6 ÂµS.